Fuzzy control scheme for energy efficiency and demand management in airports using 3D simulator - Mohamed Abdul Raouf Shafei; Mohamed Abdelazeem Tawfik; Doaa Khalil Ibrahim (Institute of Advanced Engineering and Science, 2020)
As the building sector has the largest share of energy consumption in most countries of the world, this paper focused on the study of one of the most important of the buildings which are the airports. Airports can play a major role in reducing the burden on the electrical grid as they have several factors that make them optimum models for applying energy efficiency strategies. Accordingly, the contribution in this paper is achieved by applying a Fuzzy Logic Control (FLC) scheme to improve the energy efficiency of the Egyptian airports without compromising the comfort level of the occupants and validating the obtained results by the aid of “DesignBuilder” software conducted with the “EnergyPlus” simulator, which is a state-of-the-art 3D simulator tool for checking building energy, carbon, lighting, and comfort performance. The applied 3D simulator evaluates the impacts of implementing the proposed fuzzy control system instead of ON/OFF control schemes or Building Management System (BMS). In this context, case studies were conducted at three different Egyptian airports as a high, medium, and low occupancy level airports respectively to discuss the opportunities and challenges of applying the fuzzy logic scheme in airports according to the occupancy level.